2010
DOI: 10.1111/j.1465-3362.2009.00140.x
|View full text |Cite
|
Sign up to set email alerts
|

Unrecorded consumption, quality of alcohol and health consequences

Abstract: A feasible approach for new research on the effects of unrecorded alcohol could be based on a representative sample from low socioeconomic regions with high prevalence of unrecorded consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
150
2
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(160 citation statements)
references
References 85 publications
3
150
2
4
Order By: Relevance
“…A significant effect of alcohol on SLE risk was observed in this study without accounting for the NAT2 polymorphism, although there is presently no evidence that the NAT2 enzyme could directly metabolize ethanol. Other studies have also reported an interaction between the NAT2 polymorphism and alcohol use with respect to various outcomes (53)(54)(55)(56). Therefore, the effect modification by alcohol use could be a reflection of the effect modification of the substances correlated with alcohol use, or the alcohol adding to total body burden of toxicants, so that the NAT2 enzyme and other enzymes cannot metabolize toxicants as efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…A significant effect of alcohol on SLE risk was observed in this study without accounting for the NAT2 polymorphism, although there is presently no evidence that the NAT2 enzyme could directly metabolize ethanol. Other studies have also reported an interaction between the NAT2 polymorphism and alcohol use with respect to various outcomes (53)(54)(55)(56). Therefore, the effect modification by alcohol use could be a reflection of the effect modification of the substances correlated with alcohol use, or the alcohol adding to total body burden of toxicants, so that the NAT2 enzyme and other enzymes cannot metabolize toxicants as efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…Cheapness was quoted commonly as a reason for samogon consumption [17,18]. It appears, however, that for approximately half the respondents, the main motive for consuming samogon is the belief that it is a chemically purer product than the licensed vodka.…”
Section: Discussionmentioning
confidence: 99%
“…Experts estimate that unrecorded alcohol makes up a significant share (about 25%) of all alcohol consumed in this country [12]. According to WHO definition, unrecorded alcohol include homemade informally produced alcohol, illegally produced or smuggled alcohol products, as well as surrogates alcohol that is not intended for human consumption [13]. Unrecorded alcohol in Belarus not only includes illegally produced spirits (samogon), but also legal non-beverage alcohols (surrogates), such as industrial spirits, denaturized alcohol, medicinal tinctures, perfumes [7].…”
Section: Introductionmentioning
confidence: 99%
“…The quality of alcoholic beverages may impact on health and mortality (Preedy & Watson, 2005), for instance when home-made or illegally produced alcoholic beverages are contaminated with methanol or other very toxic substances, such as disinfectants (Rehm, Kanteres & Lachenmeier, 2010). Other ingredients in alcoholic beverages, especially in beverages produced informally or illegally, have been analysed as potential causes of health problems (Kanteres et al, 2009;Lachenmeier et al, 2009;Leitz et al, 2009).…”
Section: Quality Of Alcohol Consumedmentioning
confidence: 99%